Market orientation and takaful nonfinancial performance: a strategy? - Norizan, Remli; Wan Norhayate, Wan Daud (2020)
Strategies that improve performance draw the attention of managers. The Islamic Insurance industry in Malaysia requires an emphasis on customer orientation and interfunctional coordination to improve and achieve better performance. This paper discusses the market orientation and its components, the relationship between market orientation and nonfinancial performance, and the implication of the market orientation strategy within the Takaful industry in Malaysia. Future research on a similar topic is recommended to improve a certain area such as a combination of nonfinancial and financial performance study to provide further proof of the positive impact of market orientation on the performance of Takaful business in Malaysia.